Combination of e-readiness models to assess based on system approaches at cooperatives in Indonesia - Khaerul, Manaf; Cecep Nurul, Alam; Aedah, Abd Rahman; Beki, Subaeki; Faiz, M. Kaffah (2019)
The 4.0 industrial revolution, on the one hand, will open opportunities for the domestic product market to compete internationally and vice versa. Business competition is so tight, the existence of free markets and advances in information technology, robotics, artificial intelligence, transportation, and communication are rapid, giving changes quick on the economy. The way to adapt to the outlook and the ability to project change in the environment and be able to determine the right strategy for this change is a must for organizations that are committed to survival as in Cooperatives in Indonesia. Regarding this problem, there are several e-readiness models that have been developed to test readiness or ability to provide platforms, comparisons, and estimates including TRAM (Technology Readiness and Acceptance Model) and several variables namely business content and institutional contexts that influence the model. The results show that the TRAM 2.0 model and E readiness are related to each other. The E-readiness model has 2 success factors for The McLeod and MacDonell's projects as attributes used for readiness input. From the correlation process, added a new factor, called Business Content, Institutional Context so that the E-readiness model has 8 factors.